1998
DOI: 10.1111/j.2044-835x.1998.tb00760.x
|View full text |Cite
|
Sign up to set email alerts
|

Poor readers' ability to detect speech rhythm and perceive rapid speech

Abstract: Recent research indicates that the rhythmic properties of speech may indicate to the infant listener where word boundaries are most likely to occur. However, rhythmic awareness is not included in present discussions of phonological awareness. It is suggested that skills which develop in early infancy to facilitate speech perception (i.e. awareness of rhythm) may have an impact upon later phonological development and literacy. This paper outlines a cross-sectional study, designed to examine whether poor readers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
113
0
15

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(134 citation statements)
references
References 25 publications
(59 reference statements)
6
113
0
15
Order By: Relevance
“…Indeed, children who perform well on this measure of speech rhythm (the revised mispronunciations task) are likely to be more sensitive to stress, have the ability to reverse stress patterns in two-syllable words, and be better able to identify and decode phonemes in words and match these words to those stored in the mental lexicon (Chiat, 1983;Kitzen, 2001;Wood, 2006). Sensitivity to stress may also help children to identify onset rhyme boundaries, which enables and facilitates analogy (Goswami, 2003;Goswami et al, 2002) and may also help to identify word boundaries, facilitating spoken word recognition skills and subsequent vocabulary development (Kitzen, 2001;Lindfield et al, 1999;Metsala, 1997;Wood & Terrell, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, children who perform well on this measure of speech rhythm (the revised mispronunciations task) are likely to be more sensitive to stress, have the ability to reverse stress patterns in two-syllable words, and be better able to identify and decode phonemes in words and match these words to those stored in the mental lexicon (Chiat, 1983;Kitzen, 2001;Wood, 2006). Sensitivity to stress may also help children to identify onset rhyme boundaries, which enables and facilitates analogy (Goswami, 2003;Goswami et al, 2002) and may also help to identify word boundaries, facilitating spoken word recognition skills and subsequent vocabulary development (Kitzen, 2001;Lindfield et al, 1999;Metsala, 1997;Wood & Terrell, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Holliman, Wood, and Sheehy (2008) found that performance on this task could predict a significant amount of unique variance in word reading (3.8%) in a group of early readers after controlling for age, vocabulary, phoneme deletion, and rhyme detection ability (phonological awareness). Links between speech rhythm and word reading have also been demonstrated in other recent studies involving stress manipulation and sensitivity (Gutierrez-Palma & Reyes, 2007;Holliman, Wood, & Sheehy, 2009, in press;Wood & Terrell, 1998). Goswami et al (2002) investigated whether reading difficulties are associated with deficits in perceptual rhythmic timing.…”
Section: Speech Rhythm and Word Readingmentioning
confidence: 99%
See 1 more Smart Citation
“…Así, plantean que el reconocimiento del lenguaje hablado facilita la adquisición del vocabulario, lo que a su vez fomenta el desarrollo de la CF y, por lo tanto, el de la habilidad de lectoescritura (Adams, 1990). Contemplan también que la conciencia prosódica podría afectar directamente a la CF dado que la percepción de los fonemas es más fácil en las sílabas acentuadas (Wood y Terrell, 1998). Otra forma en que la conciencia prosódica podría relacionarse con las habilidades de lectura sería mediante la conciencia morfológica, puesto que en algunas palabras cambia el acento si se añaden sufijos; la detección de estos cambios de acento facilitaría el aprendizaje de los sufijos, lo que llevaría a su vez a una mejor ejecución lectora.…”
Section: Introductionunclassified
“…Based on previous related findings reporting impaired perception of pragmatic, affective and grammatical prosody cues in ASD (see McCann & Peppé, 2003;O'Connor, 2012;Kujala et al, 2013 for reviews), it is predicted that the group with ASD would exhibit reduced performance on our syllable stress perception task compared to the comparison group. Deficits in the primary perception of syllable stress could have negative consequences in learning how different acoustic versions of utterances convey different meanings, which in turn could result in atypical receptive and expressive prosodic abilities, communication skills and overall language acquisition (Cutler, Oahan, & van Donselaar, 1997;Mehta & Cutler, 1988;Pierrhumbert, 2003, Wood & Terrell, 1998. In addition, this study aimed to investigate the associations between stress perception and communicative abilities in individuals with ASD.…”
Section: Introductionmentioning
confidence: 99%